دور الأرشيف العثماني في كتابة تاريخ الجزائر العثمانية من خلال كتابات الدكتور عبد الجليل التميمي - بقادي, مسعود (جامعة الوادي University of Eloued, 2017)
إن فترة التواجد العثماني بالجزائر والتي امتدت لأكثر من ثلاثة قرون،هي فترة حبلى بالأحداث والقضايا السياسية والاقتصادية والاجتماعية وغيرها ،وعلى اعتبار أن دراسة تاريخ وأحداث هذه الفترة تعتمد على الوثائق المادية بالدرجة الأولى فقد اهتم عدد قليل من المؤرخين المغاربة بذلك وعلى رأسهم الأستاذ المتفرد والمتمرس الدكتور عبد الجليل التميمي (أطال الله في عمره) وله في ذلك باع طويل من الدراسات التي تعتمد على الوثائق (الأرشيف) العثمانية .كيف لا وهو الذي يحسن اللغة العثمانية (كان قد درسها بإيعاز من أستاذه "كلود كاهين "claude cahen")بالإظافة الى العربية والفرنسية والانجليزية ،ولذلك ارتأيت أن تكون مقالتي هذه بعنــــــــــــــــــــــــــــــــــــــــــــــــــــــوان : دور الأرشيف العثماني في كتابة تاريخ الجزائر العثمانية من خلال كتابات الدكتور عبد الجليل التميمي وفق النقاط التالية : 1- التعريف بالمؤرخ والمفكر والباحث، الأستاذ عبد الجليل التميمي 2- أهمية الأرشيف العثماني المغاربي عامة والجزائري خاصة 3- نماذج من دراسات الأستاذ عبد الجليل التميمي للتاريخ المغاربي في الفترة العثمانية وختمت هذا المقال باستنتاجات هامة حول فترة التواجد العثماني بالجزائر بالإضافة الى مجموعة من الملاحق تخدم الموضوع. That the period of the Ottoman presence in Algeria which lasted for more than three centuries, is pregnant period the events and issues of political, economic and social, and considering that the study of the history of the events of this period depends on the physical documents primarily the few number of historians Moroccans so and headed by Professor edition veteran of Dr. Abdul Jalil al-Tamimi, may God prolong his life) and the long experience of studies based on documents (archive) Ottoman Empire, how can it not improve the Ottoman language (had studied at the behest of his mentor "Claude Kahin "claude cahen" to Arabic, French and English, therefore you decide to be my these the role of the Ottoman archives in writing the history of Algeria Ottoman Empire through the writings of Dr. Abdul Jalil Tamimi according to the following points: 1. Definition met with historian and thinker and researcher, Professor Abdul Jalil al-Tamimi 2. The importance of the Ottoman Archives General Maghreb Algerian for 3. Examples of case studies professor Abdul Jalil al-Tamimi Maghreb history in the Ottoman period and concluded this article important conclusions on the duration of the Ottoman presence in Algeria to a group of the supplements serve the Subject
Keywords: الأرشيف العثماني، الجزائر العثمانية، عبد الجليل التميمي